2023
DOI: 10.1186/s12920-023-01727-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single-cell and bulk RNA sequencing analysis identifies a neoadjuvant chemotherapy-related gene signature for predicting survival and therapy in breast cancer

Xiaojun Zhang,
Ran Feng,
Junbin Guo
et al.

Abstract: Neoadjuvant chemotherapy (NAC) is a well-established treatment modality for locally advanced breast cancer (BC). However, it can also result in severe toxicities while controlling tumors. Therefore, reliable predictive biomarkers are urgently needed to objectively and accurately predict NAC response. In this study, we integrated single-cell and bulk RNA-seq data to identify nine genes associated with the prognostic response to NAC: NDRG1, CXCL14, HOXB2, NAT1, EVL, FBP1, MAGED2, AR and CIRBP. Furthermore, we co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…CIRP expression negatively correlated with malignancy in ovarian tumors, endometrial cancers, and nasal cancers [26,27,32,71,72]. A recent study identified CIRP as one of nine genes associated with the prognostic response to neoadjuvant therapy [73]. Our observations support the role for CIRP as a tumor suppressor that reduces the progression and invasive potential of mammary gland tumors and encourages further delineation of the effects and benefits of CIRP on breast (and potentially ovarian and endometrial) cancer development and progression.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…CIRP expression negatively correlated with malignancy in ovarian tumors, endometrial cancers, and nasal cancers [26,27,32,71,72]. A recent study identified CIRP as one of nine genes associated with the prognostic response to neoadjuvant therapy [73]. Our observations support the role for CIRP as a tumor suppressor that reduces the progression and invasive potential of mammary gland tumors and encourages further delineation of the effects and benefits of CIRP on breast (and potentially ovarian and endometrial) cancer development and progression.…”
Section: Discussionsupporting
confidence: 75%
“…CIRP expression is altered in several cancers, including breast cancer. While the normal physiological role of CIRP as a stress-induced RBP has been well characterized, more recent studies have detailed the roles for CIRP in several diseases, including different forms of cancer and in inflammation [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]32,34,37,38,[40][41][42][70][71][72][73]. Our previous studies identified a role for CIRP in suppressing epithelial proliferation during mammary gland development, specifically at the transition from lactation to involution [28].…”
Section: Discussionmentioning
confidence: 99%